A highly selective fluorescent probe for detection of Cd2+ and HSO3− based on photochromic diarylethene with a triazole-bridged coumarin-quinoline group. Issue 40 (21st June 2018) - Guo, Shuli; Liu, Gang; Fan, Congbin; Pu, Shouzhi
Abstract : A novel photochromic diarylethene containing a quinoline-linked 3-aminocoumarin Schiff base unit (1O ) was synthesized and used for the selective detection of Cd 2+ and HSO3 − . Abstract : A novel photochromic diarylethene containing a quinoline-linked 3-aminocoumarin Schiff base unit (1O ) was synthesized and used for the selective detection of Cd 2+ and HSO3 − . The synthesized probe exhibited a straightforward response for the selective detection of Cd 2+ . Its fluorescence emission red-shifted ∼126 nm and was enhanced 24.9 fold in the presence of Cd 2+ . Meanwhile, the fluorescence color of1O changed from dark cyan to golden yellow. The binding stoichiometry between1O and Cd 2+ was determined to be 1 : 1. A molecular logic circuit with three inputs and one output was successfully constructed with its light and metal-responsive behaviors. In addition, 1O was able to selectively recognize HSO3 − with a 135-fold enhanced fluorescence emission and a notable fluorescence color change from dark cyan to bright cyan. The 1 H NMR and mass spectrometry analyses suggest that the HSO3 − sensing of1O is based on the hydrolysis of the Schiff base group of1O .